Indicators of adversity recorded in hospitalisation records of children aged less than 5 years or their mothers: a record linkage study of children born in England in 2011 - Toqir Mukhtar; Linda Wijlaars; Louise McGrath-Lone; Ruth Gilbert (International Journal of Population Data Science, 2018)
Background Early identification of child adversity (comprising abuse, neglect, social or material adversity) is essential to target early interventions to safeguard children, and support vulnerable families. We determined the prevalence of indicators of adversity recorded in diagnostic codes in child and/or maternal hospital admissions in England.